Narrative of an expedition to the Polar Sea, in the years 1820, 1821, 1822, & 1823, commanded by Lieutenant, now Admiral, Ferdinand von Wrangell - Vrangelʹ, Ferdinand P. (James Madden and Co., Successors to Parbury & Co., 1840)
edited by Major Edward Sabine